Pengaruh Stunting pada Kognitif Anak Usia Dini - Milla Diah Putri Nazidah; Rida Fauziah; Ruli Hafidah; Jumiatmoko Jumiatmoko; Novita Eka Nurjanah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
Stunting is a condition in which children experience growth disorders that make a child's height shorter than his age, stunting is due to severe nutritional status over time. Early childhood’s stunting may influence various aspects of a child's development, especially in cognitive aspects. There is a significant link between stunting and child cognitive development. This relates to the maturity of the central nerve organ (brain) which with the ability of a child requires balanced nutritional intake. Therefore, stunting to early childhood children is closely related to cognitive abilities. The study used literature study methods by analyzing relevant research results. The purpose of this study is to know the correlation between stunting to premature cognitive and cognitive effects in cognitive aspects. With this study it is expected that stunting prevention efforts in children's early ages will be possible through roles between teachers, parents, and society institutions from the womb to the birth of children.